Implementasi Website Kelas Untuk Pengerjaan Proyek Mata Kuliah - Yanes Robert Yeska Kakihary; Alexander Setiawan; Lily Puspa Dewi (Jurnal Infra, 2021)
Currently, the process of working on a project or group assignment from the teacher will often experience a lack of control over the process.  The whole of a group work is only seen from the results and accuracy in the collection.  In fact, in addition to results and timeliness, teachers also need to know the process of each individual to understand their level of ability.Looking at the background of the problem, an application is designed that improves individual performance control in project work or group assignments.  This application will use a special framework to solve control problems, and can manage project work management to make it better.  Applications will be created using the PHP programming language and MySQL as a database. The results obtained from this application include the creation of a working website with a framework for project control to regulate existing work processes.